Development of a Web-Based Decision Support System for Academic Program Selection Using the Weighted Product Method - Ardiansyah, Fadlan; Maharani, Riska (Journal of Technology and Computer, 2025)
In the era of digital transformation, higher education institutions face increasing demands to provide effective, data-driven tools that support student decision-making. One critical decision for prospective students is selecting an academic program that aligns with their interests, academic abilities, and future career goals. This study presents the development of a web-based Decision Support System (DSS) that applies the Weighted Product (WP) method to recommend the most suitable academic program for new university applicants. The system allows users to input criteria such as academic performance, aptitude test scores, and personal interests. These inputs are then processed using the WP method, which calculates a weighted score for each available program option. The top-ranked programs are displayed as recommendations to the user. The system was evaluated through User Acceptance Testing (UAT) involving 30 participants, and the results showed a high level of user satisfaction in terms of ease of use, accuracy, and responsiveness. This solution not only reduces subjectivity and inefficiencies in manual selection processes but also encourages informed, data-based decision-making. The implementation of this DSS demonstrates how technology can enhance educational guidance services and improve student placement outcomes in higher education.